SOFT SKILL DAN HARD SKILL ALUMNI D3 MICE UNIVERSITAS TRISAKTI DI DUNIA INDUSTRI - Aekram Faisal; Yudhaputri, Egabetha A (Universitas Trisakti, 2024)
The Tracer Study of D3 Service Management (MICE) Study Program, Faculty of Economics and Business (FEB), Trisakti University (USAKTI) aims to study the experience of D3 Service Management (MICE) alumni while studying at the study program associated with the world of work they experience today. The method of data collection in this report is presented descriptively from a questionnaire survey and has been used to see the general condition of alumni. The results of the data show that graduates generally think, for knowledge competence, that an important understanding of the courses in the curriculum can be continued and developed with technology-related input. The results show that graduates can work independently, adapt new technology, is very important to them, while for the ability to solve work problems of a nature and context that is in accordance with their field of applied expertise based on logical thinking, innovative, and responsible for the results independently is important; able to compile reports on work results and processes accurately and validly and communicate them effectively to other parties in need; Able to work together, communicate, and innovate in their work. Specific skills that are considered very important with an allocation of answers from respondents of 100% are skills to plan the concept of MICE activities, being able to determine the feasibility of a MICE activity. Devoted to God Almighty and able to demonstrate a religious attitude; Uphold human values in carrying out duties based on religion, morals and ethics. In addition, recommendations from this tracer study are expected to be used to improve the design, process and learning facilities in the D3 Service Management (MICE) FEB USAKTI Study Programme.